Pendidikan Ruhani Dalam Alquran - Subri .; Achmad Bachtiar (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
Education is a human need. Therefore, every human being must receive proper education to be able to live as a human being. In this perspective, human beings must be educated to survive in their lives amid tight competition. With the importance of education, Allah has commanded to gain knowledge as someone who has an education and a decent life.Spiritual education is an effort to purify the soul of various inclinations to purify the soul from various bad tendencies and sins, then decorate it with good deeds and praiseworthy qualities so that it is always submissive and obedient to Allah, and the attainment of the degree of piety, so the realization of morality karimah and feel always watched by Allah Swt.